(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Information plays a major role in any organization. The value ofinformation depends on its application and use. The success of an organizationlargely depends on the quality of the information that it generates. Theinformation is used as raw material for decision making. The use of ComputerBased Information System (CBIS) makes the process very effective and efficientwhen the large amounts of data are involved. Though there are several types ofinformation systems are in existence which support decision making, thedecision support system is one of them. This paper is an attempt to highlightsthe decision support system as a tool for making the better decisions in theorganization.